Prosedur Izin Checking dan Bongkar Muat Luar Kawasan MV. Gloucester Express di Bea Cukai Belawan - M. Syafri; Nurmaliana Sari Siregar (Jurnal Transformasi Bisnis Digital, 2026)
This paper aims to find out the process of issuing permits for checking and unloading cargo outside the customs area at the customs and excise office, this application must have a permit that must be fulfilled to be managed by the agent, because the implementation of checking and unloading cargo outside the designated area without obtaining a permit can be subject to criminal sanctions as regulated in Article 102 letter (b) of Law Number 17 of 2006 concerning Customs Due to port congestion, ships can dock outside the customs area (out custom area) by fulfilling certain requirements and following the procedures set by the Customs and Excise authorities. in managing permits, agents often encounter obstacles or constraints when issuing permits that are detrimental to certain parties. Therefore, the responsible party of PT. Bahari Eka Nusantara Belawan branch must coordinate and have accurate accuracy in the process of issuing this permit. The role of PT. Bahari Eka Nusantara Belawan branch is very important for parties who participate in the process of managing permits outside this area. This permit is crucial to avoid criminal charges against those responsible for checking and unloading outside the customs area. It can be concluded that there are still obstacles or errors in data input that can cause delays in approval of permits for checking and unloading outside the customs area.